2021
DOI: 10.1021/acs.jpclett.1c02995
|View full text |Cite
|
Sign up to set email alerts
|

Novel Braceletlike BiSbX3 (X = S, Se) Monolayers with an In-Plane Negative Poisson’s Ratio and Anisotropic Photoelectric Properties

Abstract: In this work, we predict two novel two-dimensional (2D) auxetic materials, BiSbX 3 (X = S, Se) monolayers, through first-principles calculations. Attributed to their special braceletlike structure, the in-plane negative Poisson's ratio (NPR) of BiSbS 3 and BiSbSe 3 monolayers are as high as −0.25 and −0.26, respectively. The phonon dispersion calculations, ab initio molecular dynamics simulations, and elastic constants calculations demonstrate that these two monolayers possess excellent dynamic, thermal, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Notably, at angles θ = 39 • , 141 • , 219 • , and 321 • , the in-plane NPR value of the AsBiTe 3 monolayer, with and without SOC reaches as high as −0.29 and − 0.25, respectively. These predicted values are comparable to that of auxetic BiSbSe 3 monolayer (−0.26) and Ga-phosphorene (−0.267) [16], and surpassing other materials such as GaPS 4 monolayer (−0.033), B 4 N (−0.032), bophorene (−0.04), penta-graphene (−0.07), and SiC 6 (−0.042) [57,[69][70][71]. This shows that the AsBiTe 3 monolayer is a flexible material.…”
Section: Mechanical Propertiessupporting
confidence: 55%
“…Notably, at angles θ = 39 • , 141 • , 219 • , and 321 • , the in-plane NPR value of the AsBiTe 3 monolayer, with and without SOC reaches as high as −0.29 and − 0.25, respectively. These predicted values are comparable to that of auxetic BiSbSe 3 monolayer (−0.26) and Ga-phosphorene (−0.267) [16], and surpassing other materials such as GaPS 4 monolayer (−0.033), B 4 N (−0.032), bophorene (−0.04), penta-graphene (−0.07), and SiC 6 (−0.042) [57,[69][70][71]. This shows that the AsBiTe 3 monolayer is a flexible material.…”
Section: Mechanical Propertiessupporting
confidence: 55%
“…Ammar et al 28 synthesized BiSbSe 3 films using a traditional direct fusion technique and explained the reduction of the optical band gap from amorphous to approximate crystalline state of BiSbSe 3 films. Guo et al 29 systematically investigated the properties of BiSbX 3 (X = S and Se) monolayers through first-principles calculations and demonstrated that the anisotropic carrier mobility and optical absorption coefficient provide a theoretical reference for their applications in electronic and optoelectronic devices. Recently, Zhan et al 30 reported that the XBiSe 3 (X = As and Sb) monolayers show high anisotropic mobility and enhanced optical absorption in the visible light region, and the AsBiSe 3 can match the conditions of the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) under 4% biaxial compression strain.…”
Section: Introductionmentioning
confidence: 99%